2013
DOI: 10.1021/ja410117q
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity Stereochemical Memory in a FeII4L4 Tetrahedral Capsule

Abstract: A new class of Fe(II)4L4 capsules, based upon a tritopic trialdehyde subcomponent, is reported. One such capsule was prepared diastereoselectively through the incorporation of a chiral amine residue. This amine was displaced by an achiral one, while maintaining the stereochemistry of the cage framework (99% ee); this cage retained its stereochemistry even after 4 days at 90 °C. Mechanistic studies indicate the memory displayed by this capsule to be the result of effective stereochemical communication between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
100
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 68 publications
7
100
0
Order By: Relevance
“…In stark contrast with the behavior of the ML 3 complexes and M 4 L 6 cages studied, the substitution of the Fe II 4 L 4 cage 7 a with ( S )‐ b was observed to occur through a cooperative imine exchange process (see Section S4), confirming the previously reported kinetic stability of this Fe II 4 L 4 framework 16b. Not being able to use cage 7 a to investigate the degree of stereochemical coupling between metal centers in M 4 L 4 structures, we turned to its Co II ‐containing congener ( 8 a ), which was not observed to undergo cooperative amine exchange (Figure S7, Figures S36–S37).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…In stark contrast with the behavior of the ML 3 complexes and M 4 L 6 cages studied, the substitution of the Fe II 4 L 4 cage 7 a with ( S )‐ b was observed to occur through a cooperative imine exchange process (see Section S4), confirming the previously reported kinetic stability of this Fe II 4 L 4 framework 16b. Not being able to use cage 7 a to investigate the degree of stereochemical coupling between metal centers in M 4 L 4 structures, we turned to its Co II ‐containing congener ( 8 a ), which was not observed to undergo cooperative amine exchange (Figure S7, Figures S36–S37).…”
supporting
confidence: 79%
“…The effect of ligand structure on the degree of stereochemical communication within tetrahedral cages was studied by examining the substitution with the same amine (( S )‐ b ) of two other Fe II cages: cage 6 a ,18 built from a longer ditopic ligand (compared to 2 a ), and cage 7   a , based upon a tritopic ligand 16b. For cage 6 b , the f 2  value of 0.45 is only slightly higher than the value of 0.40 for 2 b , verifying quantitatively the previous observation that linker length does not strongly affect the degree of stereochemical communication in these cages 17a…”
mentioning
confidence: 99%
“…Two examples of tetrahedral cages with chiral memory have been described to date. 47,83,84 As noted in the previous section, cage 6 exhibits stereochemical memory; after isolation of the diastereomeric pair and replacement of the resolving chiral counter ion by an achiral one, the structure retains enantiopurity for at least 8 months, even upon extended heating in D 2 O (Figure 9). 47 In further work, Raymond and co-workers reported an even more impressive example of chiral and structural memory in the same structure.…”
Section: Stereochemical Memory Effectmentioning
confidence: 57%
“…84 The [Fe 4 (L) 4 ] capsule 29, based upon a tritopic C 3 -symmetric trialdehyde subcomponent, was prepared diastereoselectively through the incorporation of an enantiopure amine residue, (S)-1-cyclohexylethylamine. This amine was then displaced by the achiral triamine N,N-bis(2-aminoethyl)-1,2-ethanediamine (tren), while maintaining the stereochemistry of the cage framework (Figure 10).…”
Section: Stereochemical Memory Effectmentioning
confidence: 99%
“…The tetranuclear Fe(II) cage prepared from tris(formylpyridyl)benzene and (S)-1-cyclohexylethylamine also was obtained as a ΔΔΔΔ chiral isomer. When the chiral amine subcomponent was displaced by the achiral amine tris(2-aminoethyl)amine, the cage retained its stereochemistry with high enantiomer excess (99%ee) (Figure 12) [71]. Raymond et al reported the diastereoselective formation of a tetrahedral cage assembled using six biscatecholates with chiral amide terminals and four Ga(III) cations without involving any cationic species [72].…”
Section: Dynamic Production and Inversion Of Supramolecular Chiralitymentioning
confidence: 99%